Pengaruh Profitabilitas, Debt Ratio, Opini Audit Tahun Sebelumnya, dan Ukuran Kap terhadap Opini Audit Going Concern: (Studi Empiris Pada Perusahaan Sektor Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2020-2023) - Firda Faradilla; Martini Martini (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to determine the effect of profitability, debt ratio, previous year audit opinion, and audit firm size on going concern audit opinion. The population in this study consists of companies listed in the property and real estate sector on the Indonesia Stock Exchange (IDX) for the period 2020-2023. The method used in this research is purposive sampling, with a sample of 68 companies. The analysis technique employed is logistic regression analysis, using IBM SPSS version 22 as the analysis tool. The results of this study indicate that the debt ratio and previous year audit opinion have a positive and significant effect on the going concern audit opinion, while profitability and audit firm size do not have an effect on the going concern audit opinion.